Treatment of PERItoneal disease in Stomach Cancer with cytOreductive surgery and hyperthermic intraPEritoneal chemotherapy: PERISCOPE I initial results. Issue 11 (11th April 2020) - van der Kaaij, R. T.; Wassenaar, E. C. E.; Koemans, W. J.; Sikorska, K.; Grootscholten, C.; Los, M.; Huitema, A.; Schellens, J. H. M.; Veenhof, A. A. F. A.; Hartemink, K. J.; Aalbers, A. G. J.; van Ramshorst, B.; et al.
Abstract : Background: The role of cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) in gastric cancer is unknown. This non‐randomized dose‐finding phase I–II study was designed to assess the safety and feasibility of HIPEC, following systemic chemotherapy, in patients with gastric cancer and limited peritoneal dissemination. The maximum tolerated dose of normothermic intraperitoneal docetaxel in combination with a fixed dose of intraperitoneal oxaliplatin was also explored. Methods: Patients with resectable cT3–cT4a gastric adenocarcinoma with limited peritoneal metastases and/or tumour‐positive peritoneal cytology were included. An open HIPEC technique was used with 460 mg/m 2 hyperthermic oxaliplatin for 30 min followed by normothermic docetaxel for 90 min in escalating doses (0, 50, 75 mg/m 2 ). Results: Between 2014 and 2017, 37 patients were included. Of 25 patients who completed the full study protocol, four were treated at dose level 1 (0 mg/m 2 docetaxel), six at dose level 2 (50 mg/m 2 ) and four at dose level 3 (75 mg/m 2 ). At dose level 3, two dose‐limiting toxicities occurred, both associated with postoperative ileus. Thereafter, another 11 patients were treated at dose level 2, with no more dose‐limiting toxicities. Based on this, the maximum tolerated dose was 50 mg/m 2 intraperitoneal docetaxel. Serious adverse events were scored in 17 of 25 patients. The reoperation rate was 16 per cent (4 of 25) and the treatment‐related mortality rate was 8 per cent (2 patients, both in dose level 3). Conclusion: Gastrectomy combined with cytoreductive surgery and HIPEC was feasible using 460 mg/m 2 oxaliplatin and 50 mg/m 2 normothermic docetaxel. Abstract : The PERISCOPE I study was a dose‐finding phase I–II study exploring the feasibility of gastrectomy combined with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in patients with limited peritoneal dissemination from gastric cancer. The procedure was feasible, with an intraperitoneal dose of 460 mg/m 2 oxaliplatin at 41–42°C, followed by 50 mg/m 2 docetaxel at 37°C. Feasible Abstract : Antecedentes: El papel de la cirugía citorreductora ( cytoreductive surgery, CRS) combinado con la quimioterapia intraperitoneal hipertérmica ( hyperthermic intraperitoneal chemotherapy, HIPEC) en el cáncer gástrico no está definido. Este estudio fase I‐II no aleatorizado de escalado de dosis fue diseñado para evaluar la seguridad y la viabilidad de HIPEC, después de la quimioterapia sistémica, en pacientes con cáncer gástrico con diseminación peritoneal limitada. Además, se exploró la máxima dosis tolerada ( maximum tolerated dose, MTD) de docetaxel intraperitoneal normotérmico en combinación con una dosis fija de oxaliplatino intraperitoneal. Métodos: Se incluyeron pacientes con adenocarcinoma gástrico cT3‐cT4a resecable con metástasis peritoneales limitadas y/o citología peritoneal positiva. Se utilizó una técnica HIPEC abierta con 460 mg/m 2 de oxaliplatino hipertérmico (30 minutos) seguido de docetaxel normotérmico (90 minutos) en dosis crecientes (0, 50, 75 mg/m 2 ). Resultados: Entre 2014 y 2017, se incluyeron 37 pacientes. De los 25 pacientes que completaron la totalidad del protocolo del estudio, 4 pacientes fueron tratados en el nivel de dosis 1 (0 mg/m 2 de docetaxel), 6 pacientes en el nivel de dosis 2 (50 mg/m 2 ) y 4 pacientes en el nivel de dosis 3 (75 mg/m 2 ). En el nivel de dosis 3, se produjeron dos casos de toxicidad limitante de dosis ( dose‐limiting toxicities, DLTs), ambas asociadas con un íleo postoperatorio. Posteriormente, otros 11 pacientes fueron tratados con el nivel de dosis 2, y no se produjeron más DLTs. La MTD de docetaxel intraperitoneal fue de 50 mg/m 2 . Se registraron efectos adversos graves en 17 de 25 pacientes. La tasa de reoperación fue del 16% ( n = 4) y la mortalidad relacionada con el tratamiento fue del 8% ( n = 2; ambos en el nivel de dosis 3).